Acquirit qui tuetur: Hali Meiðhad and Medieval Women’s Liberation through Virginity = Acquirit qui tuetur: Hali Meiðhad y la Liberación de la Mujer Medieval a través de la Virginidad - Rodríguez Pupo, Laura (Cuestiones de Género: de la igualdad y la diferencia, 2018)
This article joins a vibrant conversation about the concept of virginity and its relevance in the process of women’s self-liberation during medieval times. The aim of this project is to shed some light on the concept of virginity and to analyse its interpretation in a time in which it was almost compulsory to follow society’s patriarchal pattern. The study begins with a historical framework of this idea of corporeal sacredness followed by a new approach in which the contemporary perception is shattered. This article analyses the sociological and religious relevance of an idea conceived as the paramounts of holiness – thus proposing an alternative approach in which it is a defense weapon and not as a way of oppressing the female sex.